Implementasi Pendidikan Multikultural Melalui Model Contextual Teaching and Learning Pendidikan Agama Islam Siswa Sekolah Dasar (Literatur Review) (QUALITY, 2023)
Implementation of Multicultural Education through the Contextual Teaching and Learning Model of Islamic Religious Education for Elementary School Students (a Literature Review). This study aims to explain how to implement learning to foster multicultural values with a Contextual Teaching Learning approach in Islamic Religious Education, and also to explain its urgency and relevance to Islamic teachings. This research is qualitative and uses literature study methods. In the search, it was found that plurality is a logical consequence of the diversity of cultures, ethnicities, races, religions, that Indonesia has. The implementation of cultural elements is considered to be a bridge to the presence of a peaceful life. However, to make this happen, it is a tough challenge that must be faced. In fact, until now Indonesia still often faces problems in accepting diversity, especially in the midst of increasing complexity of life.Multicultural education is important to be taught to students in pluralistic Indonesia. PAI plays a role in instilling inclusive and contextual Islamic teachings using a contextual teaching and learning model that has proven successful in the process of transferring knowledge and values, so that students are able to understand and practice multicultural values that are in line with Islamic values in life such as mutual respect, respect, help, tolerance, democracy, inclusion in a heterogeneous society. Penelitian ini bertujuan untuk menjelaskan bagaimana mengimplementasikan pembelajaran untuk menumbuhkan nilai-nilai multikultural dengan pendekatan Contekstual Teaching Learning dalam Pendidikan Agama Islam, dan juga untuk menerangkan urgensi dan relevansinya dengan ajaran Agama Islam. Penelitian ini bersifat kualitatif dan menggunakan metode studi literatur. Dalam pencarian tersebut ditemukan bahwa pluralitas merupakan konsekuensi logis keragaman budaya, suku, ras, agama, yang dimiliki Indonesia. Implementasi unsur kebudayaan dianggap dapat menjadi jembatan hadirnya kehidupan yang damai. Namun, untuk mewujudkan hal tersebut, merupakan tantangan berat yang harus dihadapi. Kenyataannya sampai saat ini Indonesia masih kerap menghadapi masalah dalam menerima keberagaman terutama di tengah kompleksitas kehidupan yang semakin tinggi. Pendidikan multikultural penting diajarkan kepada peserta didik di Indonesia yang pluralistik. PAI berperan menanamkan ajaran islam yang inklusif dan kontekstual dengan menggunakan model contekstual teaching and learning terbukti berhasil dalam proses transfer ilmu dan nilai, sehingga peserta didik mampu memahami dan mengamalkan nilai-nilai multikultural yang senapas dengan nilai-nilai Islam dalam kehidupan seperti saling menghormati, menghormati, tolong menolong, toleran, demokratis, inklusif di tengah masyarakat yang heterogen.